DİVANÜ LÜGATİ'T- TÜRK'TE YER ALAN TÜRK HALK KÜLTÜRÜ ÖGELERİNİN İLKÖĞRETİM 4. VE 5. SINIF SOSYAL BİLGİLER PROGRAMLARINDA İŞLENİŞİ. - ÇENCEN, Namık (Turkish History Education Journal (TUHED), 2016)
Divan-ı Lûgati't Türk, which is written by Kasgarlı Mahmut in 1074, is a solid language and culture legacy from XI century Turkish World. With this precious work, Kasgarlı Mahmut had his name in letters of gold on not only Turkish people’s heart but also in history of Turkish language and culture, and that makes him outstanding value in our culture. In preserving Turkish cultural legacy, course programs and books have a large function. In this article, by taking high Turkish cultural elements (food culture, birth, wedding and death customs, games and entertainments) into consideration, it is going to be laid emphasis on practice of these elements in Primary Education 4th and 5th grade Social Sciences programs, and by emphasizing general aims and gains of these cultural elements, there is going to be an emphasis on practice and ratio of these in the Program. This study is qualitative and the data is collected from reviewing documents. From 8 units of 4th grade Social Sciences educational program, there are only 2 units that include cultural elements from Divan-ı Lûgati't Türk. From 8 units of 5th grade Social Sciences educational program, there is only one unit that includes cultural elements from Divan-ı Lûgati't Türk. Social Sciences course, which is thought to be helpful to pass on cultural elements: a course that aims to create sensitive individuals with awareness of cultural elements needs to focus more on Turkish Cultural Elements, according to most educator.